Efektivitas Marinasi Menggunakan Jus Buah Asam Sihala (Etlingera elatior) Teradap Kualitas Fisik dan Mikrobiologis Daging Ayam Afkir - Patriani, Peni; Hafid, Harapin (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Handling of chicken carcass after slaughter needs to be prioritized to guarantee safety and quality. One method that can be applied is marination using abundantly available spices. Sihala fruit (Etlingera etalior) is a spice that is usually used as a flavoring for arsik dishes typical of Batak, which has a slightly sour taste and fresh aroma. This study aimed to develop marination using Sihala tamarind spices to improve the physical and microbiological quality of meat of rejected layers during storage. The meat of rejected laying hens was marinated for 30 minutes using siala acid with concentrations of 0%, 15%, 30%, and 45%. Storage is carried out for 24 hours to 48 hours then, followed by physical and microbiological quality measurements. The results showed that the marination using siala acid significantly (P<0.01) improved physical quality, reducing the percentage of cooking loss, lowering the pH value, increasing tenderness, and maintaining meat moisture. Samples that were marinated using siala acid significantly (P<0.01) also experienced a decrease in microbial growth compared to the control. Overall, the best physical and microbiological qualities were the samples of culled chicken marinated using Sihala tamarind juice at a concentration of 30% and 45% during a 24-hour storage period. Marinating using siala acid fruit juice is an effective strategy to improve rejected chicken meat's physical and microbiological quality. The tamarind siala has the potential as a natural preservative in meat during storage for 48 hours.